Kesesuaian Buku Teks Matematika Siswa Kelas IX SMP Kurikulum 2013 Berdasarkan Pendekatan Saintifik - Devihana Nur Maysa; Fitrah Samsuddin, Auliaul (Cartesian: Jurnal Pendidikan Matematika, 2025)
This study aims to determine the suitability of mathematics textbooks for grade IX students with the 2013 Curriculum based on the Scientific Approach. This research is descriptive with a qualitative approach. The results showed that the suitability of the material of similarity and congruence, and curved-sided solids in the mathematics textbook for grade IX students published by Kemendikbud based on the scientific approach is as follows: at the observing stage are very suitable and suitable categories, the questioning stage are suitable and quite suitable categories, the collecting information stage are very suitable and suitable categories, the reasoning stage are very suitable categories for both materials, while at the communicating stage are very suitable and quite suitable categories. For Tiga Serangkai Publisher, the observing stage are very suitable categories for both materials, the questioning stage are not suitable categories for both materials, the information gathering stage are of suitable categories for both materials, the stages of reasoning are not suitable categories for both materials, while at the communicating stage are suitable categories for both materials. Book by Erlangga Publisher, the observing stage are very suitable and suitable categories, the questioning stage are not suitable categories for both materials, the gathering information stage are suitable and not suitable categories, the reasoning stage are suitable and not suitable categories, while the communicating stage are quite suitable and not suitable categories. Thus, it can be concluded that books that are suitable with the Scientific approach of the 2013 Curriculum are books published by Kemendikbud.